2017
DOI: 10.1002/gj.2960
|View full text |Cite
|
Sign up to set email alerts
|

Reddening of ~2.5 Ga granitoid by high‐temperature fluid linked to mafic dyke swarm in the Bundelkhand Craton, north central India

Abstract: The origin of reddening of granitoid is controversial. Red granitoids, occurring spatially with grey granitoids with a thin transitional zone is a volumetrically significant litho‐type in the Bundelkhand Craton, north central India. Using detailed petrography and microstructure study, and phase compositions and elemental X‐ray maps, we demonstrate for the first time that pervasive infiltration of Fe‐Mg‐Na‐K‐rich fluid caused re‐equilibration of ~2.5 Ga grey monzogranite during both brittle and ductile deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Before the current investigation, a general term "green-coloured vein material" was assigned to the vein infills (e.g., Sensarma et al, 2018); however, the XRD analysis and microscale observations carried out in the present study reveal that these green-coloured vein materials consist of vermiculite + epidote + quartz (Figure 6a). The most significant peaks of XRD analyses at d values 14.209 Å (41.96%), 7.097 Å (100%), Boettcher, 1966;Davies & Bisset, 1948;Johnson, 1964).…”
Section: Xrd Analysismentioning
confidence: 83%
“…Before the current investigation, a general term "green-coloured vein material" was assigned to the vein infills (e.g., Sensarma et al, 2018); however, the XRD analysis and microscale observations carried out in the present study reveal that these green-coloured vein materials consist of vermiculite + epidote + quartz (Figure 6a). The most significant peaks of XRD analyses at d values 14.209 Å (41.96%), 7.097 Å (100%), Boettcher, 1966;Davies & Bisset, 1948;Johnson, 1964).…”
Section: Xrd Analysismentioning
confidence: 83%
“…NW-SE and NE-SW are nearly coeval conjugate sets, and N-S trending deformation was the youngest among the events (Rao et al, 2005;Bhattacharya and Singh, 2013;Singh and Bhattacharya, 2017). The BGGC carries the imprints of 0.5-0.6 Ga old Pan-African event, responsible for the knife-sharp juvenile shear bands in the craton (Kaur et al, 2016;Sensarma et al, 2018). This event is preceded by the post ~2.5 Ga event of grey-granite to pink-granite transformation in the presence of fluids, which induced reactions in nominally anhydrous minerals like feldspars and increased the porosity of the granites (Putnis, 2021).…”
Section: Geologymentioning
confidence: 99%
“…The boundary between red and grey granitoid is gradational where the redcoloured granitoid fades gradually into greycoloured granitoid with progressive decrease in red colouration. Instead of considering the red and grey granitoids are of separate entities, Sensarma et al (2018) suggested that the original grey-coloured granitoid transformed to red-coloured granitoid due to mantle-derived high temperature fluid-rock metasomatic alteration. The conclusion of Sensarma et al (2018) is further supported by the observation that both grey-and red-coloured granitoids show similar modal mineralogical compositions (Sarkar et al 2017) and contemporaneous crystallisation age (Kaur et al 2016).…”
Section: General Characters Of the Bgmentioning
confidence: 99%
“…Instead of considering the red and grey granitoids are of separate entities, Sensarma et al (2018) suggested that the original grey-coloured granitoid transformed to red-coloured granitoid due to mantle-derived high temperature fluid-rock metasomatic alteration. The conclusion of Sensarma et al (2018) is further supported by the observation that both grey-and red-coloured granitoids show similar modal mineralogical compositions (Sarkar et al 2017) and contemporaneous crystallisation age (Kaur et al 2016). We, therefore, use the common term granitoid to refer to both red-and grey-coloured granitoid rocks that exhibit an undoubtedly porphyritic texture under the microscope (figure 1c).…”
Section: General Characters Of the Bgmentioning
confidence: 99%